Investigating Students’ Strategies and Difficulties in Facing TOEFL Reading Section - Pramesti, Reghina Aulia (Journal of English Language and Education, 2023)
The TOEFL test has a significant impact on EFL (English as a Foreign Language) students. It is an examination administered by the Educational Testing Service (ETS) in Princeton, New Jersey, to evaluate the English proficiency level of non-native speakers. It is the most widely used test in universities and passing it with a high score is crucial for students. To overcome challenges, various reading strategies are commonly employed to understand the information in the text. Language learners can utilize any strategy to comprehend the text, which is vital for both understanding the content and overcoming reading difficulties. The data in this study is categorized into primary data, obtained from student questionnaires, and secondary data, derived from interview results. The information was collected through questionnaires and interviews conducted with 60 students from different faculties who had taken the TOEFL test at Universitas Muhammadiyah Jember. The findings reveal that students utilize strategies such as rereading the text to enhance comprehension, using keywords to identify the main idea, and focusing on the passage's content. Additionally, students encounter challenges in responding to implied questions, primarily due to limited vocabulary and time constraints during the TOEFL reading section.